2020
DOI: 10.3390/jcm9092866
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges of OSCC Diagnosis: Salivary Cytokines as Potential Biomarkers

Abstract: Fast, economic, and noninvasive, molecular analysis of saliva has the potential to become a diagnostic tool of reference for several local and systemic diseases, oral cancer included. The diagnosis of Oral Squamous Cell Carcinoma (OSCC) can be performed using high specificity and sensibility biomarkers that can be encountered in the biological fluids. Recent advances in salivary proteomics have underlined the potential use of salivary biomarkers as early diagnosis screening tools for oral neoplasia. In this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 93 publications
(154 reference statements)
0
24
0
1
Order By: Relevance
“…Over the past two decades, the 5-year survival rate has remained at~50% due to its initially asymptomatic nature, leading to advanced stage diagnosis with few therapeutic options. 100 Although smoking, alcohol, and betel nut use are clearly associated with OLK development, the factors driving the malignant transformation of these lesions are poorly understood, and it is difficult to accurately predict whether OLK will resolve, persist or progress to OSCC. 101 The specific microbial enrichment and its metabolites associated with potentially malignant OLK could be used as novel biomarkers of malignant transformation.…”
Section: Microbial Signals In Oral Leukoplakia and Oral Squamous Cell Carcinomamentioning
confidence: 99%
“…Over the past two decades, the 5-year survival rate has remained at~50% due to its initially asymptomatic nature, leading to advanced stage diagnosis with few therapeutic options. 100 Although smoking, alcohol, and betel nut use are clearly associated with OLK development, the factors driving the malignant transformation of these lesions are poorly understood, and it is difficult to accurately predict whether OLK will resolve, persist or progress to OSCC. 101 The specific microbial enrichment and its metabolites associated with potentially malignant OLK could be used as novel biomarkers of malignant transformation.…”
Section: Microbial Signals In Oral Leukoplakia and Oral Squamous Cell Carcinomamentioning
confidence: 99%
“…Other studies have indicated an increased content of IL-1, IL-6, TNF-α in the saliva of subjects with oral squamous cell carcinoma compared to patients with dysplastic oral lesions and control groups of subjects. Because of the above, salivary cytokines provide useful information on the behavior of epithelium in carcinogenesis and may be potential biochemical markers of oral cancer [41].…”
Section: Cytokines and Markers Of Oxidative Stressmentioning
confidence: 99%
“…Druge studije su ukazale na povećan sadržaj IL-1, IL-6, TNF-α u pljuvački ispitanika sa oralnim skvamoznim karcinomom u odnosu na pacijente sa displastičnim oralnim lezijama i kontrolnim grupama ispitanika. Zbog navedenog, citokini salive pružaju korisne informacije o ponašanju epitela u karcinogenezi i mogu biti potencijalni biohemijski markeri karcinoma oralne sredine [41].…”
Section: Citokini I Markeri Oksidativnog Stresaunclassified
“…Oral malignancies include cancers that occur in the mouth, lips and pharynx, and oral squamous cell carcinoma (OSCC) accounts for over 90% of oral cancer. In 2018, OSCC accounted for 43.8% of new HNSCC cases and 37.8% of deaths [2]. Oral cancer is characterized by concealed onset, di cult diagnosis, rapid development, and is often accompanied by metastasis and destructive treatment [3].…”
Section: Introductionmentioning
confidence: 99%